Bactericidal mode of action of bedaquiline. (8th March 2015) - Hards, Kiel; Robson, Jennifer R.; Berney, Michael; Shaw, Lisa; Bald, Dirk; Koul, Anil; Andries, Koen; Cook, Gregory M.
Abstract: Objectives: It is not fully understood why inhibiting ATP synthesis in Mycobacterium species leads to death in non-replicating cells. We investigated the bactericidal mode of action of the anti-tubercular F1 Fo -ATP synthase inhibitor bedaquiline (Sirturo™) in order to further understand the lethality of ATP synthase inhibition. Methods: Mycobacterium smegmatis strains were used for all the experiments. Growth and survival during a bedaquiline challenge were performed in multiple media types. A time-course microarray was performed during initial bedaquiline challenge in minimal medium. Oxygen consumption and proton-motive force measurements were performed on whole cells and inverted membrane vesicles, respectively. Results: A killing of 3 log10 cfu/mL was achieved 4-fold more quickly in minimal medium (a glycerol carbon source) versus rich medium (LB with Tween 80) during bedaquiline challenge. Assessing the accelerated killing condition, we identified a transcriptional remodelling of metabolism that was consistent with respiratory dysfunction but inconsistent with ATP depletion. In glycerol-energized cell suspensions, bedaquiline caused an immediate 2.3-fold increase in oxygen consumption. Bedaquiline collapsed the transmembrane pH gradient, but not the membrane potential, in a dose-dependent manner. Both these effects were dependent on binding to the F1 Fo -ATP synthase. Conclusions: Challenge with bedaquiline results in an electroneutral uncoupling of respiration-driven ATP synthesis. This may be a determinant of the bactericidal effects of bedaquiline, while ATP depletion may be a determinant of its delayed onset of killing. We propose that bedaquiline binds to and perturbs the a - c subunit interface of the Fo, leading to futile proton cycling, which is known to be lethal to mycobacteria.